Pengaruh servant leadership terhadap quality of work life pada karyawan generasi milenial - Baiq Widya Ayu Ardiyanti; Nida Hasanati; Adhyatman Prabowo (Cognicia, 2021)
Indonesia is entering a demographic surplus era where millennial generation employees occupy most of the existing work opportunities. When the organization pays attention to and fulfills the needs of millennial generation employees, this arguably will prosper the employees so that their quality of work life can be realized. Organizational support provided by leaders who try to prioritize common interests over personal interests or servant leadership is one of the things that creates employees’ welfare because the employees’ needs are met. The purpose of this study was to determine the effect of servant leadership on the quality of work life of millennial generation employees. This study used quantitative methods with the sampling technique employed is using total sampling with the number of subjects in this are 96 people at BUMN X in West Nusa Tenggara. The data collection method used the servant leadership scale of 18 items and the quality of work life scale of 34 items. Data analysis used the simple linear regression technique. The results showed that there was a significant positive effect of servant leadership on the quality of work life. Servant leadership has an effect of 48.6% on the quality of work life for millennial generation employees (F = 88.893, p = 0.000, = 0.486).